علامہ اقبال کے اردو کلام میں تصور رسالت:تجزیاتی مطالعہ: The Concept of Prophethood in Allama Iqbal’s Urdu Kalam: An Analytical Study - Dr. Abdul Wajid (Seerat Studies, 2023)
Iqbal is renowned poet, thinker, and philosopher. His novel ideas gave new dimensions to Urdu poetry with the concepts developed with the passage of time. His stay in Europe played an important role in development of his thought. He dug deep into the consequences of Muslims’ down fall, which compelled him to think about the Muslims of Subcontinent. In this scenario the concept of Risalat played an important role, so we can see that the teachings and revelation of the Prophet Muhammad SAW became the central thought of his poetry. He considers the teachings of Muhammad SAW as the only solution to the problems of Muslims. He believes Muslims earned respect and honour in the world due to Islam. If Muslims want to regain the former glory, they must go back to the teachings of the Prophet SAW. Therefore his concept of Risalat is the basic source of inspiration. This article is the study of Iqbal’s Urdu poetry in the context of his concept of Risalat.